2015
DOI: 10.1128/jb.00017-15
|View full text |Cite
|
Sign up to set email alerts
|

NAD-Independent l-Lactate Dehydrogenase Required for l-Lactate Utilization in Pseudomonas stutzeri A1501

Abstract: NAD-independent L-lactate dehydrogenases (L-iLDHs) play important roles in L-lactate utilization of different organisms. All of the previously reported L-iLDHs were flavoproteins that catalyze the oxidation of L-lactate by the flavin mononucleotide (FMN)-dependent mechanism. Based on comparative genomic analysis, a gene cluster with three genes (lldA, lldB, and lldC) encoding a novel type of L-iLDH was identified in Pseudomonas stutzeri A1501. When the gene cluster was expressed in Escherichia coli, distinctiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
22
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 48 publications
1
22
0
Order By: Relevance
“…Thus, the exact functions of D-iLDH and glycolate oxidase in bacteria would require a case-by-case investigation. Furthermore, considering the important roles of iLDHs in microbial lactate utilization, the pathogenicity of several microbes lactate determination and biocatalysis processes (Iwuoha et al, 1999;Fuller et al, 2011;Gao et al, 2011;Jiang et al, 2014;Gao et al, 2015;Sheng et al, 2015), more experimental verification of iLDHs remains to be performed.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the exact functions of D-iLDH and glycolate oxidase in bacteria would require a case-by-case investigation. Furthermore, considering the important roles of iLDHs in microbial lactate utilization, the pathogenicity of several microbes lactate determination and biocatalysis processes (Iwuoha et al, 1999;Fuller et al, 2011;Gao et al, 2011;Jiang et al, 2014;Gao et al, 2015;Sheng et al, 2015), more experimental verification of iLDHs remains to be performed.…”
Section: Discussionmentioning
confidence: 99%
“…Pseudomonas is a vast bacterial genus in which various species have the ability to utilize lactate for growth (27)(28)(29). Several Pseudomonas genes related to lactate utilization have been identified, and several of these enzymes have been characterized and used in biocatalysis processes (23,(30)(31)(32)(33).…”
mentioning
confidence: 99%
“…coagulans L‐LDH at the highest degree. However, Gao et al., found that Mg 2+ exhibited the highest activation capacity for Pseudomonas stutzeri L‐LDH activity.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, when KOH and NH 4 OH were used as neutralizers, the significant increase in ldhL1 transcription was correlated with a marked reduction in optical purity of d-lactate to 93.7% and 91.3%, which suggested that only L-LDH1 was the key factor affecting optical purity of d-lactate produced by S. inulinus YBS1-5. In addition, many previous reports have revealed that l-lactate permeases are involved in l-lactate utilization in different strains (Gao et al, 2015;Jiang, Gao, Ma, & Xu, 2014). Guided by the whole-genome sequence of S. inulinus CASD, we measured the transcription levels of l-lactate permease-encoding gene (lldP) under different neutralizers.…”
Section: Changes In Ldhds and Ldhls Transcription Levels In The Prementioning
confidence: 99%